أثير أحداث الحراك الشعبي العربي على السياسةالأمريكية والصينية تجاه دول شمال إفريقيا - براهيمي, مريم (revue mofakir, 2018)
: The following research paper outlines a study to evaluate the impacts of the new emergent changes of the Chinese (PRC) and the American policies in the MENA region, I will examine the historical origins of the Sino American relations and strategies in it focusing on the new situation according to the recent geopolitics changes. Depending on the instable situation in the Middle East and North Africa the MENA region, that followed the events of the unexpected uprisings in the Arab world especially the Maghreb and North African countries such as Tunisia, Libya, and Egypt. The Arab spring events had reflected on the interests of the major powers, like the United States, European Union, Russia and China. As well as influencing Their Foreign policies, by using the wait-and- see approach to do not lose their interests in the MENA. The United States and China are important trade partners of the African countries, who are competing to achieve their various interests in the continent. We can simply observe the growing geostrategic importance of the North Africa as a region, where multiple economic and strategic interests of these two countries, becoming one of their core sources of rivalry for oil and naturel resources